Development of Opioid Peptide Analogs for Pain Relief - Janecka, A.; Perlikowska, R.; Gach, K.; Wyrebska, A.; Fichna, J. (Current Pharmaceutical Design, 2010)
Opioid receptors and opioid peptides constitute the endogenous opioid system. The most relevant function of the opioid system seems to be the inhibitory modulation of nociceptive information at supraspinal, spinal and peripheral sites, although it is also implicated in the modulation of many other processes in the body. Centrally acting plant opiates, such as morphine, are the most frequently used analgesics for the relief of severe pain, even though their undesired side-effects are serious limitation to their usefulness. Opioid peptides have the potential to be pharmaceutical agents for the treatment of pain, devoid of side-effects accompanying morphine. Unfortunately, peptides are generally hydrophilic compounds that will not enter the central nervous system via passive diffusion, due to the existence of the blood-brain barrier. Peptides are also easily degraded by proteolytic enzymes which further reduces their therapeutic value. Therefore, the design of peptide analogs based on the sequence of endogenous opioid peptides must be focused on increasing bioavailability and enhancing brain uptake.